Health Democracy Index: Development and Validation of a Self-Reported Instrument for Measuring Patient Participation in Health Policy - Souliotis, Kyriakos; Peppou, Lily E.; Agapidaki, Eirini; Tzavara, Chara (Frontiers in Public Health, 2018)
Introduction: Patient participation has emerged as a preponderant theme in contemporary health and healthcare; however there is a dearth of research on the degree and impact of collective patient participation on shaping health policy. In this frame, the current study endeavoured to validate a scale for assessing patients’ association (PA) participation in health policy processes. Furthermore, PAs’ participation in health policy decision making in Greece was explored. Materials and Methods: The Health Democracy Index (HDI) is an eight-item scale enquiring about PAs’ participation in important facets of health policy. To investigate its psychometric properties, 414 members of PAs in Greece were randomly recruited. By employing a self-reported questionnaire, construct validity was examined through exploratory and confirmatory factor analysis, while convergent validity was investigated through an additional question asking respondents to rate the degree of their association’s participation in health policy processes. Moreover, the internal consistency of the scale and its test-retest reliability were explored. Results: The scale showed high internal consistency ( Cronbach a = 0.85) and test-retest reliability (ICC = 0.89, p<0,001). Exploratory factor analysis suggested a unidimensional construct; while confirmatory factor analysis indicated an adequate fit of the one-factor model (RMSEA = 0.079, CFI = 0.976 and GFI=0.972). Regarding convergent validity, the HDI composite score displayed strong and positive correlation with the item asking respondents to rate the degree of PA participation in health policy processes ( rho = 0.73, p <0.0001). Concerning the pattern of results in Greece, PAs’ participation was found to be low. The lowest level was observed for the item enquiring about PA participation in the national parliament and the highest for panels at influential health-related organizations. Conclusion: The HDI is a valid and reliable tool that can be utilized to serve policy-related as well as research purposes. PAs’ participation in Greece is weak and thus efforts should be made to enhance it.